2D Wavelength‐Polarization Dispersive Microspectroscope Based on a Hybrid Plasmonic Helical Nanostructure. Issue 9 (2nd March 2022) - Sun, Zhiguang; Chen, Huan; Zhang, Zhenglong; Pan, Lujun; Yang, Yiming; Dong, Bin; Fang, Yurui
Abstract: Microspectrometer features remarkable portability and integration and is prospected to provide quick detection tools to daily life and revolutionize research techniques. Due to the extremely finite footprint, microspectrometer can hardly analyze the polarization feature by placing a polarizer in the optical path as conventional spectrometers. Here, a novel 2D wavelength‐polarization dispersive microspectroscope based on a carbon nanocoil with plasmonic Au nanoparticles (Au/CNC) as a dispersive component is demonstrated. The unique 2D dispersion properties of Au/CNC are examined by microspectroscopic and Fourier spatial microscopic exploration. Au/CNC disperses light as wavelength to bands of different diffraction orders like a grating along the coil axis. The wavelength of the incident light can be obtained from the location of the signal lines in a relatively large visible‐near‐infrared wavelength range. Perpendicular to the coil axis, incident light is dispersed as polarization with bright and dark areas. Therefore, the left‐ and right‐circularly polarized light can be distinguished, and polarization orientation of linearly polarized light can be obtained. This effect provides a powerful microspectrometer that simultaneously analyzes wavelength and polarization features. Moreover, this potent tool can further evolve new revolutionary techniques via integration with other systems. Abstract : Unique 2D wavelength‐polarization dispersive characteristic of Au/CNC is found. It disperses light as wavelength to bands of different diffraction orders along the coil axis, while disperses light as polarization with bight and dark areas perpendicular to the coil axis. Based on this effect, a powerful 2D wavelength‐polarization microspectrometer can be built.